Flexible electric heating material and preparation method and application thereof

By vacuum plasma treatment, grafting silicone compounds and polymer brushes on the surface of the fiber fabric, and ion exchange and metal layer deposition, a flexible electrothermal material with an integrated structure was prepared, which solved the problem of adhesion failure of flexible electrothermal films in the prior art in extreme environments, and achieved a flexible electrothermal material with high strength, adjustable heating efficiency and excellent mechanical properties.

CN119824682AActive Publication Date: 2025-04-15HARBIN INST OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510037236.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The existing flexible electric heating films are prone to failure of adhesion due to high temperature in extreme environments, resulting in unstable operation of the drive device, and uneven dispersion of heating materials and low electric heating conversion efficiency, which affects service life and reliability.

Method used

The activated fiber fabric is treated by vacuum plasma, and the silicone compound and polymer brush are grafted on its surface, and ion exchange and metal layer deposition are carried out to form a conductive path, imparting the heating function of the fiber fabric, and preparing a flexible electrothermal material with an integrated structure.

Benefits of technology

The obtained flexible electro-heating material has high strength, adjustable heating efficiency, and is closely combined with the fiber fabric and metal layer. It has excellent mechanical properties and reliability, and can maintain excellent mechanical properties and heating properties in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824682A_ABST
    Figure CN119824682A_ABST
Patent Text Reader

Abstract

The invention relates to a flexible electric heating material and a preparation method and application thereof, and belongs to the technical field of electric heating materials, the preparation method of the electric heating material comprises the following steps: S1, carrying out vacuum plasma treatment on a fiber fabric to obtain an activated fiber fabric; s2, grafting an organosilicon compound on the surface of the activated fiber fabric to obtain a first modified fiber fabric; s3, placing the first modified fiber fabric in a mixed solution containing an initiator and a polymeric monomer, carrying out a polymerization reaction, and growing a polymer brush to obtain a second modified fiber fabric; s4, placing the second modified fiber fabric in a (NH4) 2PdCl4 solution, and carrying out ion exchange to obtain a third modified fiber fabric; and S5, placing the third modified fiber fabric in a chemical plating solution, and carrying out metal layer deposition to obtain the flexible electric heating material. The prepared flexible electric heating material is high in strength, adjustable in heating efficiency and capable of keeping excellent mechanical performance and heating performance in a complex environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electric heating materials, and in particular to a flexible electric heating material and a preparation method and application thereof. Background Art

[0002] In the aerospace field, shape memory polymer composites are widely used in the drive devices of deployable structures. The traditional drive method is to adhere the electric heating film to the surface and drive the deployment through remote heating. However, this surface-adhered electric heating film is prone to adhesion failure due to high temperature during use, especially in extreme environments, debonding, resulting in unstable operation of the drive device and even possible failure. This poses a major challenge to the reliability and safety of aerospace equipment.

[0003] With the development of intelligent technology, electric heating materials have been widely used in many fields, especially flexible electric heating films, which have attracted much attention due to their thinness, softness and good folding resistance. However, there are many shortcomings in the existing flexible electric heating film technology, such as poor film adhesion, low electrothermal conversion efficiency, and uneven dispersion of heating materials. This is mainly due to the insufficient adhesion of the conductive paste on the substrate and the conductive particles coated in the resin, which leads to reduced electrothermal conversion efficiency and easily causes local overheating. In addition, the electric heating film often has uneven heating during bending and use, and even power attenuation and short circuit, which seriously affects its service life and reliability. Summary of the invention

[0004] In response to one or more technical problems existing in the prior art, the present invention provides a flexible electric heating material and a preparation method and application thereof. The flexible electric heating material prepared by the present invention has high strength and adjustable heating efficiency. The fiber fabric and the metal layer (heating layer) are tightly combined, and it has excellent mechanical properties and reliability, and can maintain excellent mechanical properties and heating properties in complex environments.

[0005] In a first aspect, the present invention provides a method for preparing a flexible electric heating material, the method comprising the following steps:

[0006] S1. The fiber fabric is subjected to vacuum plasma treatment to obtain an activated fiber fabric;

[0007] S2. grafting an organosilicon compound on the surface of the activated fiber fabric to obtain a first modified fiber fabric; the organosilicon compound is a silane coupling agent containing a carbon-carbon double bond;

[0008] S3. placing the first modified fiber fabric in a mixed solution comprising an initiator and a polymerization monomer, performing a polymerization reaction, growing a polymer brush, and obtaining a second modified fiber fabric; the polymerization monomer is a quaternary ammonium salt containing a carbon-carbon double bond;

[0009] S4. placing the second modified fiber fabric in a (NH4)2PdCl4 solution for ion exchange to obtain a third modified fiber fabric;

[0010] S5. placing the third modified fiber fabric in a chemical plating solution to deposit a metal layer to obtain a flexible electric heating material.

[0011] Preferably, the fibers in the fiber fabric are one or more of carbon fiber, glass fiber, Kevlar fiber, and polyester fiber;

[0012] The silane coupling agent containing a carbon-carbon double bond is 3-(trimethoxysilyl)propyl methacrylate;

[0013] The quaternary ammonium salt containing a carbon-carbon double bond is methacryloyloxyethyl trimethylammonium chloride; and / or

[0014] The initiator is one or more of a peroxide initiator and an azo initiator.

[0015] Preferably, the vacuum plasma treatment time is not less than 30 minutes.

[0016] Preferably, grafting an organosilicon compound on the surface of the activated fiber fabric comprises:

[0017] The activated fiber fabric is placed in an organosilicon compound solution and reacted for 1 to 2 hours; the organosilicon compound solution is obtained by mixing an organosilicon compound and a solvent; the organosilicon compound accounts for 2 to 6 vol% of the organosilicon compound solution.

[0018] Preferably, the polymerizable monomer accounts for 15-25 vol% of the mixed solution; and / or

[0019] The polymerization reaction temperature is 75-85° C. and the reaction time is 1-2 hours.

[0020] Preferably, the concentration of the (NH4)2PdCl4 solution is 3-7 mM; and / or

[0021] The ion exchange time is 20 to 40 minutes.

[0022] Preferably, the chemical plating solution comprises a metal salt, a reducing agent, a pH adjusting agent, a complexing agent, a buffer and water; and the metal salt is at least one of a copper salt and a nickel salt.

[0023] Preferably, the temperature of the metal layer deposition is 25-95° C.; and / or

[0024] The metal layer deposition rate is 2.5-5 μm / h.

[0025] The present invention provides a flexible electric heating material in a second aspect, which is prepared by the preparation method described in the first aspect.

[0026] In a third aspect, the present invention provides an application of the flexible electric heating material described in the second aspect, wherein the flexible electric heating material is compounded with a shape memory polymer to obtain a shape memory composite material, which is used to drive a deployment device.

[0027] Compared with the prior art, the present invention has at least the following beneficial effects:

[0028] The present invention first uses vacuum plasma treatment to clean the surface of the fiber fabric and generate active group hydroxyl groups on the surface of the fiber fabric to enhance the activity of the fiber fabric; then, an organosilicon compound containing a carbon-carbon double bond is grafted on the surface of the fiber fabric, and a polymerization reaction occurs with a quaternary ammonium salt containing a carbon-carbon double bond under the action of an initiator to generate a polymer brush on the surface of the fiber fabric; then [PdCl4]2- is introduced into the surface of the fiber fabric through an ion exchange reaction; finally, in the process of chemical plating, [PdCl4]2- is first reduced to Pd to provide a reaction site for the subsequent metal layer deposition process, promote the deposition of the metal layer on the surface of the fiber fabric, form a conductive path, give the fiber fabric a heating function, and finally obtain a flexible electric heating material with an integrated structure. The flexible electric heating material prepared by the present invention has high strength and adjustable heating efficiency, and the fiber fabric is tightly combined with the metal layer (heating layer), has excellent mechanical properties and reliability, and can maintain excellent mechanical properties and heating properties in a complex environment.

[0029] The flexible electric heating material provided by the present invention can be accurately cut into heating circuits by die-cutting technology, and can be integrally formed with shape memory materials to obtain shape memory composite materials with high strength, good interface bonding and adjustable heating efficiency. It can achieve stable and reliable shape memory composite material driving functions in complex environments, meet the stringent requirements of the aerospace field for shape memory composite material driving devices, and solve the problem of overheating and debonding of traditional surface-adhesive heating films. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0031] Figure 1 This is a preparation flow chart of the flexible electric heating material provided by the present invention;

[0032] Figure 2This is a resistance test diagram of the flexible electric heating material and the shape memory material before and after being combined provided by Example 4 of the present invention;

[0033] Figure 3 It is an expanded view of the shape memory material composite material obtained by combining the flexible electric heating material and the shape memory material provided in Example 4 of the present invention. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0035] In a first aspect, the present invention provides a method for preparing a flexible electric heating material, the method comprising the following steps:

[0036] S1. The fiber fabric is subjected to vacuum plasma treatment to obtain an activated fiber fabric;

[0037] S2. grafting an organosilicon compound on the surface of the activated fiber fabric to obtain a first modified fiber fabric; the organosilicon compound is a silane coupling agent containing a carbon-carbon double bond;

[0038] S3. placing the first modified fiber fabric in a mixed solution comprising an initiator and a polymerization monomer, performing a polymerization reaction, growing a polymer brush, and obtaining a second modified fiber fabric; the polymerization monomer is a quaternary ammonium salt containing a carbon-carbon double bond;

[0039] S4. placing the second modified fiber fabric in a (NH4)2PdCl4 solution for ion exchange to obtain a third modified fiber fabric;

[0040] S5. placing the third modified fiber fabric in a chemical plating solution to deposit a metal layer to obtain a flexible electric heating material.

[0041] The present invention first uses vacuum plasma treatment to clean the surface of the fiber fabric and generate active group hydroxyl groups on the surface of the fiber fabric to enhance the activity of the fiber fabric; then, an organosilicon compound containing a carbon-carbon double bond is grafted on the surface of the fiber fabric, and a polymerization reaction occurs with a quaternary ammonium salt containing a carbon-carbon double bond under the action of an initiator to generate a polymer brush on the surface of the fiber fabric; then [PdCl4]2- is introduced into the surface of the fiber fabric through an ion exchange reaction; finally, in the process of chemical plating, [PdCl4]2- is first reduced to Pd to provide a reaction site for the subsequent metal layer deposition process, promote the deposition of the metal layer on the surface of the fiber fabric, form a conductive path, give the fiber fabric a heating function, and finally obtain a flexible electric heating material with an integrated structure. The flexible electric heating material prepared by the present invention has high strength and adjustable heating efficiency, and the fiber fabric is tightly combined with the metal layer (heating layer), has excellent mechanical properties and reliability, and can maintain excellent mechanical properties and heating properties in a complex environment.

[0042] According to some preferred embodiments, the fibers in the fiber fabric are one or more of carbon fiber, glass fiber, Kevlar fiber, and polyester fiber.

[0043] According to some preferred embodiments, the silane coupling agent containing a carbon-carbon double bond is 3-(trimethoxysilyl)propyl methacrylate.

[0044] According to some preferred embodiments, the quaternary ammonium salt containing a carbon-carbon double bond is methacryloyloxyethyltrimethylammonium chloride.

[0045] It should be noted that the present invention takes 3-(trimethoxysilyl)propyl methacrylate and methacryloyloxyethyl trimethylammonium chloride as examples to illustrate the technical solution of the present invention, but not to limit it. Other silane coupling agents containing carbon-carbon double bonds and quaternary ammonium salts containing carbon-carbon double bonds are also applicable to the technical solution of the present application.

[0046] According to some preferred embodiments, the initiator is one or more of a peroxide initiator and an azo initiator; the peroxide initiator is preferably one or more of potassium persulfate, ammonium persulfate, and hydrogen peroxide; the azo initiator is preferably azobisisobutyronitrile.

[0047] According to some preferred embodiments, the vacuum plasma treatment lasts for no less than 30 minutes.

[0048] According to some preferred embodiments, grafting an organosilicon compound onto the surface of the activated fiber fabric comprises:

[0049] Placing the activated fiber fabric in an organosilicon compound solution and reacting for 1 to 2 hours; the organosilicon compound solution is obtained by mixing an organosilicon compound and a solvent; the organosilicon compound accounts for 2 to 6 vol% of the organosilicon compound solution;

[0050] According to some preferred embodiments, the solvent is obtained by mixing 95 vol% ethanol, 1 vol% acetic acid and 4 vol% water.

[0051] According to some preferred embodiments, the polymerizable monomer accounts for 15-25 vol% of the mixed solution; and / or

[0052] The polymerization reaction temperature is 75-85° C. and the reaction time is 1-2 hours.

[0053] According to some preferred embodiments, the concentration of the (NH4)2PdCl4 solution is 3-7 mM; and / or

[0054] The ion exchange time is 20 to 40 minutes.

[0055] According to some preferred embodiments, the chemical plating solution comprises a metal salt, a reducing agent, a pH regulator, a complexing agent, a buffer and water; and the metal salt is at least one of a copper salt and a nickel salt.

[0056] In some more preferred embodiments of the present invention, the third modified fiber fabric is placed in a chemical plating solution to deposit a metal layer, including: firstly placing the third modified fiber fabric in a copper chemical plating solution to deposit a copper plating layer; and then placing the third modified fiber fabric with the copper plating layer deposited in a nickel chemical plating solution to deposit a nickel plating layer. The copper layer has good electrical conductivity and the nickel layer has good thermal conductivity, so that the prepared electric heating material has both excellent electrical conductivity and thermal conductivity, and the nickel layer can effectively prevent the copper layer from being oxidized during the heating process.

[0057] According to some preferred embodiments, when depositing the copper plating layer, the copper chemical plating solution used includes a copper salt, a reducing agent, a complexing agent, a buffer and a pH adjuster; the deposition temperature of the copper layer is 25 to 30°C.

[0058] The copper salt is one or more of CuSO4·5H2O, CuCl2·2H2O, Cu(NO3)2·3H2O, preferably CuSO4·5H2O, with a concentration of 10-15 g / L; used to provide Cu 2+ A metallic copper layer is deposited.

[0059] The reducing agent is HCHO (formaldehyde), NaBH4 (sodium borohydride) or NaH2PO2 (sodium hypophosphite), preferably HCHO, with a concentration of 3 to 5 mL / L; it is used to reduce copper ions to metallic copper.

[0060] The complexing agent is EDTA-2Na (disodium ethylenediaminetetraacetate), sodium citrate or aminoacetic acid (glycine), preferably EDTA-2Na, with a concentration of 30-40 g / L; it is used to stabilize copper ions and prevent uneven deposition.

[0061] The buffer is Na2CO3 (sodium carbonate) with a concentration of 3-5 g / L; it is used to adjust the stability of the solution and control the reaction rate.

[0062] The pH regulator is NaOH (sodium hydroxide), KOH (potassium hydroxide) or NH4OH (ammonia water), preferably NaOH, with a concentration of 10-15 g / L; it is used to adjust the pH of the solution to 12-13 to ensure that the deposition reaction is carried out under alkaline conditions.

[0063] According to some preferred embodiments, when depositing the nickel plating layer, the nickel chemical plating solution used includes a nickel salt, a reducing agent, a complexing agent, a buffer and a pH adjuster; the deposition temperature of the nickel layer is 85 to 95°C.

[0064] The nickel salt is one or more of NiSO4·6H2O (nickel sulfate hexahydrate), NiCl2·6H2O (nickel chloride hexahydrate), Ni(NO3)2·6H2O (nickel nitrate hexahydrate), preferably NiSO4·6H2O, with a concentration of 20-30 g / L; used to provide Ni 2+ A metallic nickel layer is deposited.

[0065] The reducing agent is NaH2PO2·H2O (sodium hypophosphite), NaBH4 (sodium borohydride), H2PO3 - One or more of (dihydrogen phosphate), preferably NaH2PO2·H2O, with a concentration of 10 to 20 g / L; used to reduce nickel ions to metallic nickel.

[0066] The complexing agent is one or more of C4H6O6 (tartaric acid), citric acid, and EDTA, preferably C4H6O6, with a concentration of 5 to 10 g / L; it is used to stabilize nickel ions and prevent uneven deposition.

[0067] The buffer is one or more of CH3COONa (sodium acetate), sodium citrate, and K2CO3 (potassium carbonate), preferably CH3COONa, with a concentration of 15 to 20 g / L; it is used to adjust the acid-base balance of the solution to ensure uniform coating.

[0068] The pH regulator is ammonia water, which is used to adjust the pH to 4.5-5.0 to ensure that the deposition reaction is carried out under suitable acidic conditions.

[0069] According to some preferred embodiments, the temperature of depositing the metal layer is 25-95° C.; and / or

[0070] The metal layer deposition rate is 2.5-5 μm / h.

[0071] The present invention provides a flexible electric heating material in a second aspect, which is prepared by the preparation method described in the first aspect.

[0072] In a third aspect, the present invention provides an application of the flexible electric heating material described in the second aspect, wherein the flexible electric heating material is compounded with a shape memory polymer to obtain a shape memory composite material, which is used to drive a deployment device.

[0073] The flexible electric heating material provided by the present invention can be accurately cut into heating circuits by die-cutting technology, and can be integrally formed with shape memory materials to obtain shape memory composite materials with high strength, good interface bonding and adjustable heating efficiency. It can achieve stable and reliable shape memory composite material driving functions in complex environments, meet the stringent requirements of the aerospace field for shape memory composite material driving devices, and solve the problem of overheating and debonding of traditional surface-adhesive heating films.

[0074] The preparation of shape memory composite materials includes: (1) forming a heating circuit on a flexible electric heating material through a die-cutting process; (2) compounding the die-cut flexible electric heating material with a shape memory material to obtain a shape memory composite material. The die-cut flexible electric heating material and the shape memory material are compounded by an integrated molding method, so that the flexible electric heating material and the shape memory material have good mechanical synergy and ensure high strength and reliability during use. It should be noted that the flexible electric heating material and the shape memory material of the present invention can be integrated by a conventional process for preparing composite materials with fiber fabrics and resins, for example, vacuum-assisted molding.

[0075] The obtained integrated shape memory composite material is applied to the drive deployment device. When the flexible electric heating material is energized and heated, the shape memory composite material and the structure are deformed by the heat, which can make the drive device deploy. This integrated design solves the problems of weak adhesion and debonding of traditional heating films, and improves the reliability and stability of the device.

[0076] In order to more clearly illustrate the technical solutions and advantages of the present invention, the present invention is further described below in conjunction with the examples. The present invention does not specifically limit the sources of the reagents used in the examples and comparative examples, and the reagents can be directly purchased or synthesized by themselves.

[0077] Example 1

[0078] S1. The carbon fiber fabric was placed in a vacuum plasma chamber for 30 minutes to obtain an activated carbon fiber fabric;

[0079] S2. The activated carbon fiber fabric is placed in an organic silicon compound solution at room temperature for reaction for 1 hour to obtain a first modified carbon fiber fabric; wherein the organic silicon compound solution is obtained by dissolving 3-(trimethoxysilyl)propyl methacrylate in a solvent, wherein 3-(trimethoxysilyl)propyl methacrylate accounts for 4 vol% of the organic silicon compound solution, and the solvent is obtained by mixing 95 vol% ethanol, 1 vol% acetic acid and 4 vol% deionized water;

[0080] S3. After the first modified carbon fiber fabric was rinsed with deionized water, it was immersed in a solution containing potassium persulfate and methacryloyloxyethyl trimethyl ammonium chloride (20 vol%) and polymerized at 80 ° C for 1 hour to obtain a second modified carbon fiber fabric;

[0081] S4. The second modified carbon fiber fabric is immersed in a (NH4)2PdCl4 solution with a concentration of 5 mM for 30 minutes to perform an ion exchange reaction to obtain a third modified carbon fiber fabric.

[0082] S5. Place the third modified carbon fiber fabric into a chemical deposition tank containing a copper chemical plating solution, deposit a copper layer at 25°C for 1 hour; place the material after the copper layer is deposited into a chemical deposition tank containing a nickel chemical plating solution, deposit a nickel layer at 85°C for 2.3 hours to obtain a flexible electric heating material; wherein the concentration of CuSO4·5H2O in the copper chemical plating solution is 10 g / L, the concentration of HCHO is 3 mL / L, the concentration of EDTA-2Na is 30 g / L, the concentration of Na2CO3 (sodium carbonate) is 3 g / L, and the pH is adjusted to 12 with NaOH solution; the concentration of NiSO4·6H2O in the nickel chemical plating solution is 20 g / L, the concentration of NaH2PO2·H2O is 10 g / L, the concentration of CH3COONa is 15 g / L, the concentration of C4H6O6 (tartaric acid) is 5 g / L, and the pH is adjusted to 4.5 with aqueous ammonia.

[0083] Embodiments 2-5 of the present invention are substantially the same as Embodiment 1, and the differences are shown in Table 1.

[0084] Table 1. Comparison of parameters of the preparation process of Examples 1-5 of the present invention

[0085]

[0086] It can be seen from Table 1 that by adjusting the electroplating time to control the thickness of the coating, the resistivity of the flexible electric heating material can be adjusted, and then the heating effect can be adjusted to meet different usage requirements.

[0087] The present invention combines the flexible electric heating material obtained in Example 4 with the shape memory material by vacuum assisted molding to obtain a shape memory composite material. Figure 2It can be seen that the resistance of the flexible electric heating material before and after the composite is unchanged, which shows that the resistance of the flexible electric heating material is stable, and the introduction of the shape memory material will not affect the resistance of the flexible electric heating material. Figure 3 It can be seen that when the flexible electric heating material is powered on and heated, the shape memory composite material can be fully unfolded in 14 seconds, which can meet the use requirements of shape memory composite material drive devices in the aerospace field.

[0088] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a flexible electric heating material, characterized in that: The preparation method comprises the following steps: S1. The fiber fabric is subjected to vacuum plasma treatment to obtain an activated fiber fabric; S2. grafting an organosilicon compound on the surface of the activated fiber fabric to obtain a first modified fiber fabric; The organosilicon compound is a silane coupling agent containing a carbon-carbon double bond; S3. placing the first modified fiber fabric in a mixed solution comprising an initiator and a polymerization monomer, performing a polymerization reaction, growing a polymer brush, and obtaining a second modified fiber fabric; The polymerizable monomer is a quaternary ammonium salt containing a carbon-carbon double bond; S4. placing the second modified fiber fabric in a (NH4)2PdCl4 solution for ion exchange to obtain a third modified fiber fabric; S5. placing the third modified fiber fabric in a chemical plating solution to deposit a metal layer to obtain a flexible electric heating material.

2. The preparation method according to claim 1, characterized in that: The fibers in the fiber fabric are one or more of carbon fiber, glass fiber, Kevlar fiber, and polyester fiber; The silane coupling agent containing a carbon-carbon double bond is 3-(trimethoxysilyl)propyl methacrylate; The quaternary ammonium salt containing a carbon-carbon double bond is methacryloyloxyethyl trimethylammonium chloride; and / or The initiator is one or more of a peroxide initiator and an azo initiator.

3. The preparation method according to claim 1, characterized in that: The vacuum plasma treatment time is not less than 30 minutes.

4. The preparation method according to claim 1, characterized in that: Grafting an organosilicon compound on the surface of the activated fiber fabric comprises: The activated fiber fabric is placed in an organosilicon compound solution and reacted for 1 to 2 hours; the organosilicon compound solution is obtained by mixing an organosilicon compound and a solvent; the organosilicon compound accounts for 2 to 6 vol% of the organosilicon compound solution.

5. The preparation method according to claim 1, characterized in that: The polymerizable monomer accounts for 15-25 vol% of the mixed solution; and / or The polymerization reaction temperature is 75-85° C. and the reaction time is 1-2 hours.

6. The preparation method according to claim 1, characterized in that: The concentration of the (NH4)2PdCl4 solution is 3-7 mM; and / or The ion exchange time is 20 to 40 minutes.

7. The preparation method according to claim 1, characterized in that: The chemical plating solution comprises a metal salt, a reducing agent, a pH adjusting agent, a complexing agent, a buffer and water; the metal salt is at least one of a copper salt and a nickel salt.

8. The preparation method according to claim 1, characterized in that: The temperature of the metal layer deposition is 25-95° C.; and / or The metal layer deposition rate is 2.5-5 μm / h.

9. A flexible electric heating material, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.

10. An application of the flexible electric heating material according to claim 9, characterized in that: The flexible electric heating material is compounded with a shape memory polymer to obtain a shape memory composite material, which is used to drive a deployment device.

Citation Information

Patent Citations

  • A composite electrically conductive fiber and a preparing method thereof

    CN107541953A

  • Flexible metal glass fiber cloth lithium ion battery current collector and preparation method thereof

    CN117317242A

  • Carbon fiber fabric-based flexible electrode and preparation method thereof

    CN118957994A

  • Conductive composites

    US20070116979A1

  • Carbon fiber fabric cleaning and finishing

    US20160326691A1